THE MANUFACTURER LOOKS AT HIS COST OF DISTRIBUTION. - Atwood, Paul W. (The Accounting Review, 1934)
This article focuses on the cost of distribution from the manufacturer's point of view. Distribution costs involve the total cost of carrying goods from producer to consumer, the costs of operating retail stores, the costs of operating wholesale houses, transportation costs and the manufacturer's selling costs. The author's remarks today are concerned chiefly with the cost of distribution from the standpoint of the manufacturer. When the individual manufacturer sets out to find ways and means of reducing his distribution expense, one of the first questions that canes to his mind is how do his costs compare with those of other manufactures in his industry selling the same or a similar type of product. And it was in an attempt to aid in answering this question that the Association of National Advertisers undertook a few months ago to assemble distribution cost figures from representative manufacturers in leading industries of the country. It was hoped that we could provide a yardstick by which each individual manufacturer could determine whether or not his own costs of distribution were in line with those his competitors.